2020
DOI: 10.3390/ejihpe10040066
|View full text |Cite
|
Sign up to set email alerts
|

Toxicities Caused by Head and Neck Cancer Treatments and Their Influence on the Development of Malnutrition: Review of the Literature

Abstract: Malnutrition poses a significant problem for oncology patients, resulting in fatalities within this population. Patients with head and neck cancer (HNC) are at high risk, with up to 90% developing malnutrition. Common treatments used for HNC can often lead to adverse side effects, including oral health conditions, gastrointestinal upsets, and several metabolic changes. Consequently, treatments can cause inadequate nutritional intake, resulting in a reduction in energy consumption, and alterations in energy uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 88 publications
0
16
0
1
Order By: Relevance
“…Nonetheless, our observations regarding the interplay between nutritional status, mucositis toxicity, and interruption events among patients with HNC undergoing CCRT remain inconsistent with those of previous studies. Some investigations showed that patients with optimal nutritional status suffer less from mucositis toxicity [69,70], and those with less incidence of treatment-related toxicity experience fewer treatment interruption events [9,[71][72][73][74]. Russo et al reviewed the relationship between RT breaks and oral mucositis, and reported that nutritional counseling and diet therapy-such as nutritional supplements and feeding tube placement-could reduce mucositis toxicity and the resulting treatment interruption in patients with HNC undergoing RT or CCRT [9].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, our observations regarding the interplay between nutritional status, mucositis toxicity, and interruption events among patients with HNC undergoing CCRT remain inconsistent with those of previous studies. Some investigations showed that patients with optimal nutritional status suffer less from mucositis toxicity [69,70], and those with less incidence of treatment-related toxicity experience fewer treatment interruption events [9,[71][72][73][74]. Russo et al reviewed the relationship between RT breaks and oral mucositis, and reported that nutritional counseling and diet therapy-such as nutritional supplements and feeding tube placement-could reduce mucositis toxicity and the resulting treatment interruption in patients with HNC undergoing RT or CCRT [9].…”
Section: Discussionmentioning
confidence: 99%
“…surgery, RT, CT, or their combination) can often lead to consequences (e.g. dysphagia and xerostomia) that further complicate and challenge oral intake of food, with additional deleterious consequences on nutritional status (45).…”
Section: Oral Nutritional Supplementsmentioning
confidence: 99%
“…Medical professionals and cancer patients alike believe toxicities are inevitable and general amelioration techniques are often overlooked. Difficulty eating and malnutrition during cancer therapy are common problems that can be assessed with many tools [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. The challenge is to have an acceptable quality and quantity of nutrient intake with minimal toxicity without compromising effective cancer treatment.…”
Section: Drug Combinationsmentioning
confidence: 99%
“…Malnutrition in cancer patients is a common problem. There are many indices and tools to define malnutrition, cachexia, and sarcopenia [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]62,[69][70][71][72][73][74][75][76][77]. Although weight loss from the time of diagnosis is one measure, the quantity and quality of food in the diet and information from the patient generated subjective global assessment (PG-SGA) tool can provide more specific information [35,36,45,51,62,66,[69][70][71][72][73][78][79][80].…”
Section: Review Of Strategies To Improve Eating Behaviors While Receiving Chemotherapy And/or Radiationmentioning
confidence: 99%